Quantifying the mechanisms of rain-triggered seismicity in karstic regions - Perrochet, Léa; Preisig, Giona; Valley, Benoît (Frontiers in Earth Science, 2023)
Seismicity following heavy rainfall events is often considered to be triggered by the pore pressure diffusion front migrating from the surface towards focal depth, assuming a homogeneous crust.Although this assumption can be justified in some cases depending on local geology (e.g. homogeneously fractured basement) it is too simplistic for known karst areas. Indeed, the hydraulic behaviour of karst during a flood event is not dominated by pressure diffusion, but by highly transmissive karst conduits. This generates rapid and large variations in hydraulic head, and if karstification extend towards depth, this leads to large changes in pore pressure at seismogenic depth. We consider the conditions and data from three different case studies with karstic features in order to evaluate possible seismicity triggering mechanisms. We identify four potential mechanisms to explain the influence of rainfall on fault stability : crustal loading and its associated poro-elastic deformation, pore pressure diffusion and direct hydraulic connection.We quantify the effect of these mechanisms for parametrisation corresponding to our case studies, by considering the specific features of karst and using simplified analytical solutions.Results show that pore pressure increase resulting from the crustal loading and poro-elastic deformation are much smaller than pore pressure increase resulting from a direct hydraulic connection and its diffusion towards depth over small distances. Moreover, the timing between the intense precipitations and the beginning of seismicity may indicate on the mechanism behind the triggering process: no time lag to a time lag of a few hours supposes a direct hydraulic connection, a time lag of a few hours to a few days suggest a coupled solution of a rapid pressure increase resulting from direct hydraulic connection followed by the diffusion process prograding towards focal depth. Our results highlight the importance of considering the intrinsic properties of karst and its spatial distribution, especially its extend towards depth, when studying rain-triggered seismicity in a karstic environment.